Cytogenetic Evolution of Human Ovarian Cell Lines Associated with Chemoresistance and Loss of Tumorigenicity - Stéphanie Struski; Martine Doco‐Fenzy; Michael Koehler; Ilse Chudoba; Francis Levy; Linda Masson; Nicole Michel; Evelyne Ulrich; Nadine Gruson; Jean Bénard; Gérard Potron; Pascale Cornillet‐Lefebvre (Analytical Cellular Pathology)
In order to identify genomic changes associated with a resistant phenotype acquisition, we used comparative genomic hybridization (CGH) to compare a human ovarian cell line, Igrov1, and four derived subcell lines, resistant to vincristine and presenting a reversion of malignant properties. Multicolor FISH (Multiplex‐FISH and Spectral Karyotype) and conventional FISH are also used to elucidate the karyotype of parental cell line. The drug‐resistant subcell lines displayed many chromosomal abnormalities suggesting the implication of different pathways leading to a multidrug resistance phenotype. However, these cell lines shared two common rearrangements: an unbalanced translocation der(8)t(8;13)(p22;q?) and a deletion of the 11p. These chromosomal imbalances could reflected the acquisition of the chemoresistance (der(8)) or the loss of tumorigenicity properties (del(11p)). Colour figure can be viewed on http://www.esacp.org/acp/2003/25‐3/struski.htm.